PENEGAKAN HUKUM TINDAK PIDANA KORUPSI DALAM KONSTRUKSI CONCURSUS REALIS DENGAN TINDAK PIDANA PENCUCIAN UANG (Studi Kasus Putusan Nomor : 43/Pid.Sus-TPK/2022/PN Jkt.Pst) - Saut Horas Tamba; Mompang L. Panggabean; Hendri Jayadi (Bajang Institute, 2026)
The increasing number of corruption crimes accompanied by money laundering in Indonesia has resulted in significant losses to state finances. This study aims to: (1) analyze whether law enforcement against perpetrators of corruption accompanied by money laundering in the context of concursus realis in Decision Number: 43/Pid.Sus-TPK/2022/PN.Jkt.Pst has fulfilled the sense of justice; and (2) examine the judicial considerations and the court’s decision in imposing criminal sanctions based on the legal construction philosophy of concursus realis. This research employs a normative juridical method with a statute approach and a case approach. The results show that the imprisonment sentence of 5 (five) years imposed on the Defendant, Johan Darsono, is disproportionate to the substantial financial losses suffered by the state, and therefore may be regarded as failing to satisfy public sense of justice and insufficient to create a deterrent effect. The judges’ considerations in this case relied more heavily on factual and non-juridical aspects, while juridical considerations particularly Supreme Court Regulation (Perma) No. 1 of 2002 concerning sentencing guidelines for offenders proven to have violated Article 2 and Article 3 of the Anti-Corruption Law were not fully taken into account in determining the punishment. As a result, the integration of law enforcement between corruption and money laundering offenses has not yet been optimal in realizing justice and a strong deterrent effect